Body mass index and all‐cause mortality among older adults. Issue 10 (29th August 2016) - Cheng, Feon W.; Gao, Xiang; Mitchell, Diane C.; Wood, Craig; Still, Christopher D.; Rolston, David; Jensen, Gordon L.
Abstract : Objective: To examine the association between baseline body mass index (BMI, kg/m 2 ) and all‐cause mortality in a well ‐ characterized cohort of older persons. Methods: The association between BMI (both as a categorical and continuous variable) and all‐cause mortality was investigated using 4, 565 Geisinger Rural Aging Study participants with baseline age 74.0 ± 4.7 years (mean ± SD) and BMI 29.5 ± 5.3 kg/m 2 over a mean of 10.9 ± 3.8 years of follow ‐ up. Results: The relationship between BMI (as a continuous variable) and all‐cause mortality was found to be U‐shaped ( P nonlinearity <0.001). Controlling for age, sex, smoking, alcohol, laboratory values, medications, and comorbidity status, underweight (BMI <18.5 kg/m 2 ) individuals had significantly greater adjusted risk of all‐cause mortality than persons of BMI 18.5 to 24.9 kg/m 2 (reference range). Participants with overweight (BMI 25.0–29.9 kg/m 2 ) and class I obesity (BMI 30.0–34.9 kg/m 2 ) had significantly lower adjusted‐risk of all‐cause mortality. Those with classes II/III obesity (BMI ≥ 35.0 kg/m 2 ) did not have significantly greater adjusted‐risk of all‐cause mortality. Findings were consistent using propensity score weights and among never‐smokers with 2‐ and 5‐year lag analysis and among those with no identified chronic disease. Conclusions: A U‐shaped association was observed between BMI and all‐cause mortality with lower risk among older persons with overweight and class I obesity in comparison with those with BMI 18.5 to 24.9 kg/m 2 .